Evaluasi Penggunaan Obat Rumah Tangga di Kabupaten Bandung dan Kabupaten Bandung Barat - Ida Erna Widiawati; Indra Permana; Sri Setiatjahjati (Lembaga Pengembangan Kinerja Dosen, 2026)
Irrational drug use in the community remains a significant health problem. Different geographic and demographic characteristics can influence drug use patterns and the problems that arise. This study aims to evaluate and compare household drug use patterns between Bandung Regency and West Bandung Regency. The study was conducted in January 2026 using a cross-sectional method with a door-to-door approach in Ibun Village (Bandung Regency, n=44) and Cibodas-Langensari Village (West Bandung Regency, n=26). Data were collected through structured interviews covering drug types, usage problems, and education provided. Analysis was conducted descriptively and comparatively. Significant differences were found between the two regions. Bandung Regency was dominated by analgesic-antipyretic drugs (34.1%) for acute diseases, while West Bandung Regency had more antihypertensive drugs (14.6%) and antidiabetic drugs (8.0%) for chronic diseases (45.1% of households owned chronic disease medications). The problem of incorrect dosage in West Bandung Regency (76.9%) was significantly higher than in Bandung Regency (31.8%). Non-prescription drug use was higher in Bandung Regency (31.8% vs. 11.5%). Education was tailored to the problem profile of each region. Differences in health profiles and drug use patterns between the two regions require tailored intervention approaches. Bandung Regency requires education on prescription drug use and access to healthcare, while West Bandung Regency requires a specific program for chronic disease management and intensive drug dosage education.